Peranan account officer (AO) dalam memberikan pelayanan dan meningkatkan loyalitas nasabah pada PT. BPR Ciledug Dhana semesta di tengah pandemi corona virus disease 2019 - Pradipta, Firli Yoga; Toni, Ahmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Bank Perkreditan Rakyat (BPR) is a Bank that conducts business activities conventionally or based on sharia principles, which in its activities does not provide services in payment traffic, BPR activities are much narrower when compared to the activities of commercial banks because BPR is prohibited from receiving current deposit, foreign exchange activities, and insurance. The number of People's Credit Banks (BPR) is now making competition more intense and vying for the best rating in the eyes of the public, especially PT. BPR Ciledug Dhana Semesta. Therefore, a good anlisis strategy is needed by each bank to increase profit and have good quality. This study aims to determine the role of Account Officers in increasing customer loyalty at PT. BPR Ciledug Dhan in the midst of the 2019 corona virus disease pandemic. This study uses a descriptive analysis method, which describes the overall role of the Account Officer at PT. BPR Ciledug Dhana Semesta. The results of the study indicate that customer needs can be met properly until customers are satisfied with their services so that customer loyalty occurs so that BPR does not lose customers causing substantial losses or loss of income as well as utilizing digital technology to facilitate customer needs. The purpose of all of this is of course to maintain financial system stability, so that the interests of the community and the interests of the national economy are maintained, especially in the banking world.